Maize, sunflower and barley sensitivity to residual activity of clomazone in soil (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2012)
Sensitivity of maize, sunflower and barley to clomazone residues in loamy soil was assessed in the study using bioassay. Clomazone was applied at a series of concentrations from 0.12 to 12 mg a.i./kg of soil. After 14 days, morphological (shoot height, fresh and dry weight) and physiological (content of carotenoids, chlorophyll a and chlorophyll b) parameters were measured. The results showed that morphological parameters are not valid indicators of clomazone sensitivity. Based on the results showing inhibition of the physiological parameters, I50 values were calculated and used to estimate the difference in sensitivity between the species tested. Sunflower was the most sensitive species, while the difference in sensitivity between maize and barley was not significant.Nomenclature: clomazone (2-(2-chlorbenzyl)-4,4-dimethyl-1,2-oxazolidin-3-one), maize (Zea mays L.), sunflower (Helianthus annuus L.), barley (Hordeum vulgare L.)
Keywords: Bioassays; Sunflower; Soil; Maize; Clomazone; Chlorophylls; Barley